Resolutions regarding the Beveridge Report
1943-02-22 1943 1940s 2 pages 7. That copies of these resolutions be sent to:- The Executive Committee of the N.U.A.W. The District Organiser of the N.U.A.W. The Exucutive [Executive] Committee of the Labour Party. The Trades Union Congress. The editor of the "Land Worker". The editor of the "Daily Herald". The editor of the ''News Chronicle". The editor of "Reynold's News". The editor of the "Manchester Guardian". The editor of the "New Leader". Yours sincerely, John E. Radcliffe Branch Chairman. [ ] Barnes Branch Secretary. 292/150.5/5/145